Vicinal difluorination as a C=C surrogate: an analog of piperine with enhanced solubility, photostability, and acetylcholinesterase inhibitory activity - Lizarme-Salas, Yuvixza; Ariawan, Alexandra Daryl; Ratnayake, Ranjala; Luesch, Hendrik; Finch, Angela; Hunter, Luke (Beilstein Journal of Organic Chemistry, 2020)
Piperine, a natural product derived from peppercorns, has a variety of biological activities that make it an attractive lead compound for medicinal chemistry. However, piperine has some problematic physicochemical properties including poor aqueous solubility and a susceptibility to UV-induced degradation. In this work, we designed an analog of piperine in which the central conjugated hydrocarbon chain is replaced with a vicinal difluoroalkane moiety. We show that this fluorinated analog of piperine has superior physicochemical properties, and it also has higher potency and selectivity towards one particular drug target, acetylcholinesterase. This work highlights the potential usefulness of the threo-difluoroalkane motif as a surrogate for E-alkenes in medicinal chemistry.
Keywords: Alzheimer's disease; bioisostere; conformational analysis; gauche effect; stereoselective synthesis